Theorizing state crime - Gascón, Daniel (Police and state crime in the Americas, 2024)
Today, while they are among the few, there are sociologists and criminologists who have taken the collective actions of the state as their principal subject of inquiry. Postcolonial and southern theories chart a path that future criminologists can follow in conducting research that addresses the imperial roots of the social sciences and the contemporary impacts and legacies of that history. The conversation that follows brings together Guillermina Seri, a political scientist, and Tyler Wall, a sociologist, who currently study state crime from transdisciplinary perspectives. They both explain how researchers can study police power and state crime, how to recognize the collective victims of these actions, and how to identify the leading figures and intellectual traditions that have most influenced their approach to the study of state crime.